2015
DOI: 10.1186/s12947-015-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nicorandil on microvascular function in patients with ST segment elevation myocardial infarction undergoing primary PCI

Abstract: BackgroundNicorandil, as a selective potassium channel opener, has dual action including coronary and peripheral vasodilatation and cardioprotective effect through ischemic preconditioning. Considering those characteristics, nicorandil was suggested to reduce the degree of microvascular dysfunction.MethodsThirty-two patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention (pPCI) were included in the study. Index of microvascular resistance (IMR) was measured in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Chen et al analyzed intracoronary administration of nicorandil (2 mg) and showed that it could effectively treat the NRP [ 4 ]. In a previously published study by Kostic et al, intracoronary administration of nicorandil in patients with STEMI undergoing primary PCI significantly improved microvascular function by reducing the microvascular resistance index and increasing coronary flow reserve [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al analyzed intracoronary administration of nicorandil (2 mg) and showed that it could effectively treat the NRP [ 4 ]. In a previously published study by Kostic et al, intracoronary administration of nicorandil in patients with STEMI undergoing primary PCI significantly improved microvascular function by reducing the microvascular resistance index and increasing coronary flow reserve [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that IMR is responsive to the effects of treatments known to have favorable cardiovascular effects, including vasodilators 51 and anti-ischemic 52 therapies. During PCI, compared with a direct stenting approach without initial balloon angioplasty, a predilatation step to disrupt and modify the plaque before stenting is associated with a higher IMR at the end of the PCI procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Studies have shown that intracoronary nicorandil ameliorated microvascular dysfunction, which was evaluated with IMR, and improved CFR in patients with STEMI undergoing primary percutaneous coronary intervention. [ 59 , 60 ] In addition, nicorandil may improve chest pain symptoms, and regulate plasma NO and ET-1 in the coronary slow flow. [ 61 ]…”
Section: Discussionmentioning
confidence: 99%